Implementasi Desain Pembelajaran Di Sdn 15 Tangerang - Magdalena, Ina; Rohmah, Nafisah Nur; Asmoro, Shifa Nur (ANWARUL, 2023)
To overcome the problems found in learning in the 21st century, innovative and creative solutions are needed. Of the various media that have existed to date, learning video media is one of the learning media that can be used as an option to be applied in overcoming learning problems in the 21st century. Learning design through interactive video is a media that presents audio and visuals that contain good learning messages that contains concepts, principles, procedures, theory of knowledge application to help understand a learning material. In research that discusses the implementation of learning designs at SDN 15 Tangerang, which has switched from conventional models to interactive learning designs, it uses a research model in the form of a case study. To increase the effectiveness of the learning process, a learning innovation will be developed, namely by developing learning videos. The results showed that there was an increase in knowledge of 24.42% and skills regarding the material by 23.47%. That way, it can be shown that through the use of interactive learning videos it can improve the completeness and learning outcomes of students at SDN 15 Tangerang.